Chemical analysis of the Triticum aestivum Cropped Soil - Budhathoki, Narendra Pratap Singh; Gaire, Shyam (Dhaulagiri Journal of Contemporary Issues, 2023)
Triticum aestivum commonly known as wheat. Simple random sampling method was used for collection of samples from twenty different locality of Tarakhola Rural Municipality-1, Majhakharka. The chemical compositions (NPK, Zn, B, and organic matter), EC and pH of Tarakhola Rural Municipality had been investigated. The micronutrients (Zinc and Boron) were determined by using Spectrophotometer and Colorimetric method. Nitrogen, Phosphorous and Potassium were analyzed by Kjeldahal method, Flame Photometer method, Modified Olsen’s bicarbonate method respectively. Organic matter was determined by Calorimeter. Nitrogen- 0.57%, Phosphorus-29.05 ppm (65.08kg/hector), Potash-159.68 ppm (357.69kg/hector), organic matter-3.57%. pH is 6.4 which is suitable pH for wheat crop, Electrical conductivity is 0.087ds/m (87 milisimen), Zinc-0.54 ppm, Boron is 0.01 ppm. Organic matter and Nitrogen were medium but P and K were maximum and Zn and B were minimum.